Pendidikan Karakter Religius Dalam Pembelajaran Pancasila dan Kewirausahaan Pada Mahasiswa Calon Guru MI/SDIT - Muhammad Isnaini; Isran Bidin; Misharti Misharti; Bambang Wahyu Susanto; Ilham Hudi (Departement of Mathematics Education, 2023)
This study aims to find out: 1) How do lecturers in Pancasila and entrepreneurship courses plan religious character education for MI/SDIT prospective teacher students; 2) How can MI/SDIT teacher candidates take advantage of learning religious character education in Pancasila and entrepreneurship courses and develop it so that it is realized in a reel idea in the real world; 3) How do MI/SDIT teacher candidates assess character education in learning Pancasila and entrepreneurship that is very important so that it leaves an imprint in their hearts; 4) How do MI/SDIT teacher candidates realize the value of religious character in entrepreneurship courses through commerce with God. The research method used is descriptive qualitative. The subjects in this study were PGMI UMRI Pekanbaru teaching staff. Based on the results of the study it can be concluded as follows. 1) Lecturers in the Pancasila and Entrepreneurship courses have planned character education for MI/SDIT teacher candidates properly and internalized in the IQF curriculum and designed according to the indicators in the SNP-PT guidelines. 2) Prospective MI/SDIT teachers who are currently studying at UMRI PGMI follow the implementation of character education properly. 3) MI/SDIT teacher candidates assess character education very well as character improvement in the study program environment.